Impact of corporate governance and earnings management on value relevance of accounting metrics - Chang, Chee Fei (2011)
The growing incidence of corporate failures has significantly reduced shareholder wealth and pension funds, and caused financial crisis in many economic powerhouses and the emerging markets. Regulators point out that these failures are attributed to accounting scandals and mismanagement driven by managerial opportunism. Besides fraud and conspiracy, the causes of such failures are not exceptional; misinvestments,breaches in governance control and creative (or even imaginative) accounting which threatens the reliability and usefulness of accounting information in controlling and monitoring management efficacy and safeguarding shareholder interest. Following these corporate failures, relevant authorities have implemented a series of radical reforms to restore investors’ confidence. For instance, the development of corporate governance codes and practices, amendments to the securities law and convergence of international accounting standards in Malaysia after the 1997-1998 economic crisis. This study examines the impact of corporate governance and income smoothing incident on the reliability of accounting metrics available from the published financial reports and how the equity market prices these attributes. In addition this study also examines the overall effectiveness of the governance and financial reporting reforms implemented after crisis by the authorities to improve transparency, financial integrity and value relevance of accounting information. This study deploys the regression-variation and dynamic portfolio-return models modified from well established theoretical and applied research frameworks in the prior literature. Inferences are drawn from the panel data empirical models as to assess the informativeness of accounting metrics under different specifications (e.g., economic conditioned-governance/ earnings management extended regressions and factor loading approaches). The sample size of this study covers 323 (317 for return models) firms listed on Bursa Malaysia with complete and continuous 15-year accounting and corporate governance data, and 168-month stock prices (for dynamic portfolio- return model) beginning from 1993 to 2007. In overall, the inferences from the governance extended specifications and the dynamic portfolio-return model reveal that corporate governance attributes are value- relevant in general. The test results show that governance interacted-accounting metrics are informative, and the association between these metrics and firms’ market prices and returns is statistically significant (price model: summed coefficient = 0.475, p= 0.008; return model: earnings response coefficient = 1.427, p = 0.001). In addition, the test statistics generated from the governance-controlled accounting based portfolio-return model reveal that after the economic crisis, governance control mechanism is empirically relevant to firms’ market risk premium which subsequently determines their market value (coefficient = 0.344, p = 0.000). Likewise, the information content of the accounting metrics produced by firms’ with prevalence earnings management sign is significantly negative after the crisis (price model:summed coefficient = -0.729, p = 0.002; return model: summed coefficient = -0.790,p = 0.000), implying that investors are becoming more cautious of accounting fraud in ‘managed earnings’ firms. Similar results are observed in the economic conditioned-earnings management extended dynamic accounting based portfolio-return regression specification. In many instances, the results from the earnings management extended specifications cohere harmoniously with the inferences from the corporate governance extended value relevance models. These outcomes are perhaps attributable to increased investors’ awareness on the negative impact of managerial opportunistic behaviour, and improved investors’ confidence after the crisis due to the regulatory reform in corporate governance and financial reporting environment. Interestingly, the explanatory power of firm’s book value is gaining more significance after the crisis (economic conditioned-extended price model: coefficient = 0.172, p= 0.003). Besides,inferences drawn from firms with low governance control show that accounting earnings relevancy has significantly decreased after the crisis period. This implies that earnings performance is perceived to be less reliable due to potential accounting manipulation, and thus book value is a more prudent alternative measure of firm’s performance. The results of this study provide reasonable evidence on the effectiveness of the post-crisis reforms in corporate governance and reporting environment implemented by the regulators to improve the reliability and investors’ reliance on firms’ financial performance indicators, and thus might provide insights for regulation and standard setting in the future. Besides, this study reveals the meaningful valuation effect of managerial opportunism and the importance of ex-ante efficient contracting and ex- post governance control to firms’ reliability of accounting information content and market pricing decision. This study also substantiates empirical procedures to check the robustness of governance and earnings management attributes against accounting metrics reliability and modifications to the regression-variation and dynamic portfolio-return models for corporate governance and earnings management specifications.